A Review of the perspective on the implementation of evolutionary algorithms in cyber security on IoT infrastructure - Soto-Soto, Jesus E.; Hernandez-Vega, Jose Isidro; Silva Trujillo, Alejandra Guadalupe; Reynoso-Guajardo, Luis Alejandro; Hernandez-Santos, Carlos; Gallardo-Morales, Mario Carlos (International Journal of Combinatorial Optimization Problems and Informatics, 2025)
The rapid growth of the Internet of Things (IoT) in industrial environments has increased efficiency but also heightened vulnerability to sophisticated cyber-attacks. Traditional cyber security approaches are insufficient to protect critical infrastructure, creating a need for dynamic, adaptive solutions. Evolutionary algorithms (EAs), owing to their ability to explore large search spaces and optimise parameters, offer a promising route to enhancing IoT security. This review highlights the integration of EAs with deep-learning techniques to improve intrusion detection and system resilience. Building on this background, we propose an adaptive cyber-security framework that leverages evolutionary optimisation and continual learning to detect, prevent and mitigate attacks in real time. The study emphasises the importance of validating hybrid models in real-world settings and of optimising computational efficiency. Future work should investigate autonomous response mechanisms and the scalability of solutions for large-scale Industrial IoT (IIoT) deployments, ensuring robust protection against emerging threats and aligning academic advances with industry needs. Smart citations: https://scite.ai/reports/10.61467/2007.1558.2025.v16i4.1023